THE EFFECT OF BREED AND BODY CONDITION SCORE ON OVARIAN WEIGHT, NUMBER OF FOLLICLES, AND OOCYTE QUALITY IN RETIRED COWS - Putri, Natalie Lovena Pramono; Ikhsan, Dilla Amalia Bilqis; Raharjo, Dadik; Khairullah, Aswin Rafif; Lestari, Tita Damayanti; Mustofa, Imam; Rimayanti, Rimayanti; Safitri, Erma; Amrullah, Muhammad Fajar; Ilmi, Laily 'Ulya Nurul; Pasang, Gabriel Sampe; Supriyadi, Supriyadi (Jurnal Kedokteran Hewan, 2025)
The aim of this study was to determine whether breed and body condition score (BCS) can influence ovarian weight, follicle number, and oocyte quality. This study used 90 ovaries from 15 Friesian Holstein crossbreed, 15 Ongole crossbreed, and 15 Limousin crossbreed cows obtained from an abattoir. Before the ovaries were taken, the BCS of the cows was determined. The BCS system used in this study is BCS with a scale of 1 to 5. Ovaries were weighed, follicles were measured and grouped by size (2 mm, 2-6 mm, 6 mm) then counted, oocytes were aspirated from the follicles then observed under a microscope. Oocyte quality was observed and then grouped into grade A, B, C, D based on cumulus oocyte complex (COCs). Data were analyzed using two way ANOVA and chi square test. The results of the analysis showed that breed did not influence ovarian weight, but influenced the number of follicles, and oocyte quality. In Friesian Holstein crossbreed cows, BCS affects ovarian weight, follicle number, and oocyte quality. In Ongole crossbreed cows, BCS had no effect on ovary weight, but did affect follicle number and oocyte quality. In Limousin crossbredcows, BCS had no effect on ovary weight and follicle number, but did affect oocyte quality.